Hydraulic Conductivity of Compacted Laterite Treated with Iron Ore Tailings - Umar Sa’eed Yusuf; Matawal Danladi Slim; Elinwa Augustine Uchechukwu (Advances in Civil Engineering)
The objective of this study was to investigate the effect of iron ore tailings (IOT) on hydraulic conductivity of compacted laterite. The IOT conforms to ASTM C 618-15 Type F designations. In the present study, soil was admixed with 0–20% IOT and compacted at moulding water content ranging from 10 to 25% using four types of compactive efforts. Hydraulic conductivities of the compacted soil-IOT mixtures were determined using deionized water and municipal solid waste leachate as the permeant fluids, respectively. Deionized water was the reference permeant fluid. Results of this study showed that hydraulic conductivity decreased with increase in IOT content as a result of improvement in mechanical properties of the soil. Permeation of the soil-IOT mixtures with leachate caused the hydraulic conductivity to drop to less than 1 × 10−9 m/s especially at higher compactive efforts. Also, bioclogging of the soil pores due to accumulation of biomass from bacteria and yeast present in the leachate tends to significantly reduce the hydraulic conductivity. From an economic point of view, it has been found from the results of this study that soil specimens treated with up to 20% IOT and compacted at the British Standard Light (BSL) compactive effort met the maximum regulatory hydraulic conductivity of less than or equal to 1 × 10−9 m/s for hydraulic barrier system.